Pengaruh Kualitas Kehidupan Kerja terhadap Kinerja Pegawai Melalui Kepuasan Pegawai - Muhammad Virza Alridho; Zulfina Adriani; Rts. Ratnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research is aimed at examining the influence of the quality of work life variable on employee performance and job satisfaction as a moderating variable in the IPC Pelindo II Jambi City. Data collection was carried out by distributing questionnaires with a Likert scale to 70 IPC Pelindo II Jambi City employees. Data testing used includes measurement model testing (outer model) and structural model testing (inner model) using the SmartPls 3 application. The results of the research show that the quality of work life has a positive and significant effect on employee performance at IPC Pelindo II Jambi City, quality of work life has a positive and significant effect on job satisfaction at IPC Pelindo II Jambi City, job satisfaction has a positive and significant effect on employee performance at IPC Pelindo II Jambi City, and quality of work life has a positive and significant effect on employee performance through job satisfaction at IPC Pelindo II City Jambi. Therefore, it is recommended that companies from the quality of work life aspect need to encourage employees to convey ideas and suggestions, from the job satisfaction aspect there needs to be a periodic review of the salary structure to ensure employees feel appreciated according to their contribution, from the performance aspect the company is able to provide incentives for employees who are able to complete more tasks than the set target.